Multi-variable assessment of green stormwater infrastructure planning across a city landscape: Incorporating social, environmental, built-environment, and maintenance vulnerabilities - Homet, Kate; Kremer, Peleg; Smith, Virginia; Strader, Stephen (Frontiers in Environmental Science, 2022)
Green stormwater infrastructure (GSI) is an increasingly popular tool to meet federal water regulations for stormwater quality and quantity, while assuaging urban flooding. While cities across the United States implement GSI into their planning processes, they are also potentially affecting the local communities that are receiving these GSI through social, ecological, physical, and economic impacts. Flooding is impacting urban communities by damaging homes and infrastructure, degrading ecosystems, and exacerbating social inequities. In the planning process, there is an acute need for the consideration of the equitable distribution of GSI in addition to technical and engineering needs. This study examines multiple aspects of vulnerability to local flooding impacts—social, environmental, and infrastructural—across a city landscape to identify those communities that have a greater need for GSI. Given the city of Philadelphia is a leader in GSI implementation in the United States, we use it as our research setting where we create citywide, multifaceted vulnerability indices that account for the spatial distribution of social, built environment, and maintenance vulnerabilities to flooding events. In addition to these indices, a GSI type decision table was created to suggest more equitable placements of different GSI types based on their maintenance needs and expected co-benefits. The results of this study reveal unequal distribution of social and built-environment vulnerabilities in the city at the Census block group scale, with high social vulnerability consistently spread across the central, southwest, and northwest neighborhoods of Philadelphia. Potential areas of severe GSI maintenance impacts appear to be concentrated in the downtown neighborhoods, while overall vulnerability appears elevated throughout the downtown and northwest neighborhoods. These results indicate that some communities in Philadelphia are highly vulnerable and should be prioritized for GSI implementation. In addition, the type of GSI implemented should be optimized to address the specific vulnerability impacts in different areas. A multifaceted vulnerability approach to planning can be applied in multiple areas of climate adaptation equity, with future studies continuing to update and add more dimensions of vulnerability where and when applicable.